PELAKSANAAN FUNGSI KECAMATAN DALAM PELAYANAN PUBLIK SEBAGAI ORGANISASI PERANGKAT DAERAH (OPD) DI KECAMATAN TIGAPANAH KABUPATEN KARO TAHUN 2017-2018 - Kacaribu, Franchonero; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by law no. 23 of 2014 on local government in which there is a change in the position of the sub-district as a Regional Government into a Regional Device Organization Regency or City and indirectly changes some of the duties and functions and authorities of the sub-district in running its government. The formulation of problems in this research is how the function of the sub-district in public services as a Regional Device Organization in the district Tigapanah Karo Regency.This study aims to explain the function of the sub-district in public services as a Regional Device Organization and describe the state of public services and know the factors inhibiting the function of the sub-district as a Regional Device Organization in the district tigapanah Karo Regency. The method used in this research is descriptive research with qualitative approach. Research data types are primary and secondary data. Data collection techniques in this research are documentation and interviews. Data analysis techniques used are qualitative data analysis.The results showed that the function of the sub-district as a Regional Device Organization has changed in accordance with the change in the position of the sub-district in accordance with Law No. 23 of 2014 where the sub-district receives the delegation of duties and functions and authorities under the previous district government of the sub-district is part of the central government in the region. Implementation of sub-district functions in public services in Tigapanah sub-district in terms of quality of service, tigapanah sub-district has not shown the implementation of efficient and effective services. Seen from the slow service process, and the lack of serving officers and educational background that is still underprivileged and district facilities and infrastructure are inadequate to produce services that ultimately hinder the running of excellent services.Â Keywords : Sub-district Functions, Public ServicesÂ